2010
DOI: 10.1002/cbic.201000381
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Protein Crowding in Liposomes: A New Vista for the Origin of Cellular Metabolism

Abstract: One question in the origin of life is the time at which membrane compartments came into the picture as hosts for the first forms of metabolism. If we assume the proteins and nucleic acids came first, then it is difficult to conceive how all the macromolecular components could have been entrapped at a later time in a single compartment. On the other hand, the hypothesis that metabolism originated from inside the compartment means that we would then have to conceive semipermeable, sophisticated membranes in preb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
151
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(161 citation statements)
references
References 19 publications
8
151
0
Order By: Relevance
“…In this case, where multiple co-encapsulation events occur, the "anomalous entrapment" phenomenon (seen before for single molecular species [13,19]) acts by creating nanoscale liposomes containing hundreds of different molecules in a very small volume.…”
Section: General Strategymentioning
confidence: 96%
See 1 more Smart Citation
“…In this case, where multiple co-encapsulation events occur, the "anomalous entrapment" phenomenon (seen before for single molecular species [13,19]) acts by creating nanoscale liposomes containing hundreds of different molecules in a very small volume.…”
Section: General Strategymentioning
confidence: 96%
“…It is more difficult to perform similar studies in submicron vesicles, where it is expected, however, a higher diversity due to the enhancement of stochastic events at a smaller scale. Quite interestingly, two recent studies demonstrated that when 200 nm (diameter) lipid vesicles are prepared in presence of single macromolecular species, like ferritin [13] or ribosomes [14], the solute encapsulation does not follow the expected behavior. It resulted, instead, in a dramatic dichotomy between many "empty" vesicles and few "super-crowded" ones (having an internal solute concentration up to 60 times higher than the expected value).…”
Section: The Encapsulation Of Solutes Inside Lipid Vesiclesmentioning
confidence: 99%
“…The internal structure of large multilamellar vesicles, obtained by the freeze-dry method, was studied by quantitative measurements of gene expression (84). The encapsulation of the PURE system inside small unilamellar vesicles of 100 nm in diameter revealed a strong heterogeneity of the entrapment below the micrometer size (85,86). Amphipathic peptides, which insert spontaneously into lipid bilayers, and autonomous pore-forming proteins have proven to work when they are expressed inside synthetic vesicles (87).…”
Section: Bottom-up Development Of An Artificial Cell: Broad Consideramentioning
confidence: 99%
“…In fact, it has been recently discovered that a large heterogeneity exist in a population of vesicles prepared by these methods (Dominak & Keating, 2007;Lohse et al, 2008). A clear-cut evidence of superconcentration of proteins inside lipid vesicles has been reported in the case of ferritin (Luisi et al, 2010).…”
Section: The Technology For Building Minimal Cellsmentioning
confidence: 99%
“…What is important is the demonstration that sets of free molecules and lipids spontaneously assemble into a cell-like particle, and that functions -initially not present in the bulk phase, become characteristic of compartmentalized systems. For example, the recently reported discovery (Luisi et al, 2010) of self-concentration of proteins (and ribosomes, Souza et al, submitted manuscript) inside liposomes points to the emergence of functional cells from diluted compounds. In other words, the formation of liposomes implies the formation of concentrated/segregated phase that might exhibit enhanced functionality when compared with the analogous system in bulk (see also Souza et al, 2009).…”
Section: Potential Applications Of Minimal Semi-synthetic Cells and Omentioning
confidence: 99%